2018
DOI: 10.1186/s13059-018-1443-z
|View full text |Cite
|
Sign up to set email alerts
|

Expanded base editing in rice and wheat using a Cas9-adenosine deaminase fusion

Abstract: Nucleotide base editors in plants have been limited to conversion of cytosine to thymine. Here, we describe a new plant adenine base editor based on an evolved tRNA adenosine deaminase fused to the nickase CRISPR/Cas9, enabling A•T to G•C conversion at frequencies up to 7.5% in protoplasts and 59.1% in regenerated rice and wheat plants. An endogenous gene is also successfully modified through introducing a gain-of-function point mutation to directly produce an herbicide-tolerant rice plant. With this new adeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
309
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(323 citation statements)
references
References 32 publications
7
309
0
7
Order By: Relevance
“…Two types of base editors have now been developed: cytosine base editors (CBEs)-cytidine deaminase fused with catalytically impaired Cas9-can efficiently convert a C-G base pair to a T-A pair, while adenine base editors (ABEs)-Cas9 nickase (nCas9) plus engineered Escherichia coli adenosine deaminase (TadA)enable A-T to G-C conversions (Gaudelli et al, 2017;Kim, 2018). Both CBEs and ABEs have been applied successfully in plants such as Arabidopsis, wheat and rice (e.g., Hua et al, 2018Hua et al, , 2019Li et al, 2018). However, potential base editing targets remain restricted by the requirement for protospacer adjacent motif (PAM) sequences around these sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two types of base editors have now been developed: cytosine base editors (CBEs)-cytidine deaminase fused with catalytically impaired Cas9-can efficiently convert a C-G base pair to a T-A pair, while adenine base editors (ABEs)-Cas9 nickase (nCas9) plus engineered Escherichia coli adenosine deaminase (TadA)enable A-T to G-C conversions (Gaudelli et al, 2017;Kim, 2018). Both CBEs and ABEs have been applied successfully in plants such as Arabidopsis, wheat and rice (e.g., Hua et al, 2018Hua et al, , 2019Li et al, 2018). However, potential base editing targets remain restricted by the requirement for protospacer adjacent motif (PAM) sequences around these sites.…”
mentioning
confidence: 99%
“…To extend Cas9-recognized sites, several groups have engineered Cas9 variants with amino acid substitutions and modified PAM sequences. Using these Cas9 variants in base editors could expand the scope of base editing sites (Endo et al, 2019;Hu et al, 2018;Hua et al, 2019;Nishimasu et al, 2018). Engineered SpCas9s, SpCas9-NG variants and xCas9 variants that can recognize NG as PAM have been reported recently (Hu et al, 2018;Nishimasu et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the sgRNA providing targetspecificity, the dCas9-base editors can create point mutations in the target DNA with high specificity and precision. This new technology was quickly adopted in plants, including watermelon (Lu and Zhu 2017;Li et al 2018a;Ren et al 2018;Tian et al 2018). Table 1 summarizes published reports of genome editing in fruit crops.…”
Section: Overview Of Crispr/cas9mentioning
confidence: 99%
“…Through seven rounds of extensive directed evolution and protein engineering of the bacterial tRNA adenine deaminase TadA, researchers produced an adenine base editor (ABE7.10), which efficiently converts AT to GC base pairs in a programmable manner with very high product purity in human cells . Several independent groups have reported that the ABE7.10 editor efficiently induced AT to GC base pairs at a broad range of endogenous target sites in the rice genome …”
Section: Crispr/cas9‐created Mutations In Plantsmentioning
confidence: 99%